The Participatory Budgets Implementation on the Example of Selected Municipalities - Binda, Jacek; Niedziela, Sylwia (Economy of Regions, 2021)
In recent years, participatory budgets are one of the most dynamically developing institutions of social participation. The implementation of the participatory budget in local government units is an endeavor to increase the degree of involvement of the inhabitants of a given community to co-decide on spending budget funds. Implementation of a participatory budget requires a well-constructed procedure, which will engage the highest possible number of residents and lead to a more rational and efficient utilisation of budget resources of local government units. We analysed the problems of the implementations of participatory budgets in the Polish communes of Jaworze, Cieszyn, Kçty and Bielsko-Biala (South of Poland) and discussed challenges, which accompanied this process. We hypothesised that the complicated and ambiguous participatory budget procedure is the reason for a low efficiency of spending funds under participatory budgets in the analysed communes. The analysis was based on the literature review of amendments to Polish legislation that define the notion of the participatory budget and lay foundations for its functioning. We compared various constituents of the procedure applied in the examined communes, used in the process of the participatory budget implementation. Research results indicated that the participatory budget model should be changed to optimise expenditure of local funds, increase local community satisfaction and accelerate the development of the commune. The results may be used to assess the effectiveness of the spending of funds under the participatory budget in other municipalities of the region.